2021
DOI: 10.1080/23322039.2021.1911767
|View full text |Cite
|
Sign up to set email alerts
|

International trade and economic growth in Africa: The role of the digital economy

Abstract: This paper examines the role the digital economy plays in international trade impacts on Africa's economic growth based on 53 countries' sample from 2000-2018. We further divided the sample into five sub-regions, and the results are estimated by POLS, random and fixed effects, and the GMM models. The findings showed that (1) trade only has positive effects on economic growth when interacted with the digital economy in the POLS estimations, (2) Trade has a significantly positive impact on economic prosperity wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…Secondly, from the perspective of economic growth, unlike the effect on carbon emissions, the development of the digital economy makes a stable contribution to economic growth, as evidenced by many existing studies [ 56 , 57 , 58 ]. As an emerging economic form, the digital economy itself is part of the overall economy, so it is obvious that the development of the digital economy has a positive impact on economic growth.…”
Section: Econometric Tests Of the Impact Of The Digital Economy On Ca...mentioning
confidence: 99%
“…Secondly, from the perspective of economic growth, unlike the effect on carbon emissions, the development of the digital economy makes a stable contribution to economic growth, as evidenced by many existing studies [ 56 , 57 , 58 ]. As an emerging economic form, the digital economy itself is part of the overall economy, so it is obvious that the development of the digital economy has a positive impact on economic growth.…”
Section: Econometric Tests Of the Impact Of The Digital Economy On Ca...mentioning
confidence: 99%
“…It is important to point out that the analysis is carried out exclusively from the perspective of nutrient needs, i.e., of the components of food rather than the whole (An analysis focused on components is not new in economic studies. Heckscher (1933) and Ohlin (1919) did it by analysing international trade from the perspective of production factors and not of the products themselves [26]. This perspective allowed a better understanding of international trade compared to the comparative advantages proposed by Ricardo.).…”
Section: Cases Of Interestmentioning
confidence: 99%
“…* There is no recommended daily dose as the amounts required are very small.Sources:[14,25,26,27,28]. .…”
mentioning
confidence: 99%
“…Porteous (2020) and Kizito et al (2012) found no significant relationship between an export ban and domestic prices. The literature acknowledged that international trade could offer great opportunities for economic growth (Abendin & Duan, 2021). However, the potential benefits of international trade on growth are influenced by the production systems' environmental conditions.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Maize production is at the center of global food security and one of the most How to cite this paper: Amponsah, R., Kong, X. M., & Abendin, S. (2021). The Impact of Maize Trade on the Development of the Maize Industry in Ghana.…”
Section: Introductionmentioning
confidence: 99%